1988
DOI: 10.1063/1.100173
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth of ErAs on (100)GaAs

Abstract: Successful growth of (100)ErAs single-crystal films on (100)GaAs has been demonstrated. Reflection high-energy electron diffraction, low-energy electron diffraction (LEED), and Rutherford backscattering with channeling indicate single-crystal growth. LEED from the ErAs shows a (1×1) structure. Overgrowth of GaAs on ErAs is found to be difficult due to the GaAs not wetting the ErAs surface and hence resulting in island growth. For a 150-Å-thick film metallic behavior is observed with resistivities 17 and 70 μΩ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(54 citation statements)
references
References 16 publications
3
51
0
Order By: Relevance
“…They claimed that the conduction electrons exhibit almost d character; thus the exchange interaction depends on the amount of overlapping between d wave functions. Palmstrøm et al [50] successfully grew single-crystal ErAs fi lms on GaAs in 1988. Later magneto-transport measurements showed that ErAs is a low-density semimetal that magnetically orders at low temperature (4.5-4.8 K) [51].…”
Section: Early Experiments and Theoretical Studiesmentioning
confidence: 99%
“…They claimed that the conduction electrons exhibit almost d character; thus the exchange interaction depends on the amount of overlapping between d wave functions. Palmstrøm et al [50] successfully grew single-crystal ErAs fi lms on GaAs in 1988. Later magneto-transport measurements showed that ErAs is a low-density semimetal that magnetically orders at low temperature (4.5-4.8 K) [51].…”
Section: Early Experiments and Theoretical Studiesmentioning
confidence: 99%
“…ErAs is a semimetal that has the cubic rock salt structure ( † a ErAs = 0.573 nm) and is known to grow epitaxially on arsenide semiconductors with the zincblende structure [5], such as GaAs and In 0.53 Ga 0.47 As ( † a GaAs = 0.56538 nm and † a In 0.53 Ga 0.47 As = 0.5869 nm). The atomic structure of epitaxial layered ErAs/GaAs heterostructures and of epitaxial ErAs nanoparticle/semiconductor composites has been studied experimentally and theoretically [5][6][7][8][9][10][11]. For example, it has been shown that the As sublattice is continuous across the interface in both types of heterostructures [9,11].…”
mentioning
confidence: 99%
“…In the light of channeling experiments performed on Er-implanted [17], MBE grown GaAs:Er, doping at the impurity level [18], and in ultra thin ErAs layers in GaAs [19], an interstitial location of optically active Er seems to be well established. However, the reasons of such unexpected correlation remains unclear.…”
Section: Erbium In Iii-v Compoundsmentioning
confidence: 99%